2023
DOI: 10.3389/fonc.2023.1122811
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and recurrent significance of SII in patients with pancreatic head cancer undergoing pancreaticoduodenectomy

Abstract: BackgroundTo investigate the clinical significance of preoperative inflammatory status in patients with pancreatic head carcinoma (PHC), we performed a single-center study to assess it.MethodWe studied a total of 164 patients with PHC undergoing PD surgery (with or without allogeneic venous replacement) from January 2018 to April 2022. Systemic immune-inflammation index (SII) was the most important peripheral immune index in predicting the prognosis according to XGBoost analysis. The optimal cutoff value of SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The systemic inflammatory response has been shown to promote cancer progression and contribute to different stages of tumor development, including initiation, invasion, angiogenesis, and metastasis ( 42 ). In recent years, the association between the SII and the prognosis of various cancer types has been extensively investigated, demonstrating its potential as a prognostic indicator, particularly for predicting survival outcomes in patients with malignant tumors ( 16 , 17 , 19 25 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The systemic inflammatory response has been shown to promote cancer progression and contribute to different stages of tumor development, including initiation, invasion, angiogenesis, and metastasis ( 42 ). In recent years, the association between the SII and the prognosis of various cancer types has been extensively investigated, demonstrating its potential as a prognostic indicator, particularly for predicting survival outcomes in patients with malignant tumors ( 16 , 17 , 19 25 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The systemic inflammatory response has been shown to promote cancer progression and contribute to different stages of tumor development, including initiation, invasion, angiogenesis, and metastasis (42). In recent years, the association between the SII and the prognosis of various cancer types has been extensively investigated, demonstrating its potential as a prognostic indicator, particularly for predicting survival outcomes in patients with malignant tumors (16,17,(19)(20)(21)(22)(23)(24)(25)27). SII has been identified as a valuable prognostic indicator for numerous solid tumors, including hepatocellular carcinoma, pancreatic cancer, gallbladder cancer, bile duct cancer, gastric cancer, laryngeal cancer, endometrial cancer, non-small cell lung cancer, and bladder cancer, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SII is calculated by combining lymphocyte count, neutrophil count, and platelet count. SII is a good indicator of the level of immune‐inflammatory response in the body of a tumor patient, according to several studies, 19 , 37 SII is frequently used to help determine prognostic risk in tumor patients. Elevated SII values may indicate increased immune system activity and heightened inflammatory response, which is typically associated with a poor prognosis, including shorter survival and higher rates of disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…By incorporating 164 patients with pancreatic cancer who had resections and a cutoff SII value of 563, Chen et al. 37 found that the high SII group was a separate risk factor for OS, individuals with a worse prognosis and a lower SII had extensive recurrence, only TNM staging was revealed to be an independent predictive predictor for patient recurrence, the researchers speculate that this could be because tumor development and peripheral immune status are tightly related. Widely used in the investigation of various cancers, SII has been linked to poorer overall survival, tumor‐specific survival, and recurrence‐free survival according to Li et al.…”
Section: Discussionmentioning
confidence: 99%